Acetic acid treatment causes renal inflammation and chronic kidney disease in mice - Terumasa Hashimoto; Keita Shibata; Kazuo Honda; Koji Nobe (Elsevier, 2021)
We established a novel mouse model of chronic kidney disease (CKD) using acetic acid and compared it with the 5/6-nephrectomized mouse model. In our novel model, significant increases were observed in blood biochemical values and urinary parameters. Moreover, a decrease in creatinine clearance (Ccr) was observed. This model also demonstrated a higher survival rate than the 5/6-nephrectomized model. Observed histological changes in our model included cell infiltration in the renal interstitium, tubular dilation, regenerated tubules, and glomerulosclerosis. Inflammation of the renal interstitium was particularly remarkable. TNF-α, IL-1β, and ICAM-1 mRNA expression were up-regulated prior to elevation of mean blood pressure and prior to changes in blood biochemical values and urinary parameters. Up-regulation of TGF-β mRNA and down-regulation of nephrin mRNA were also observed at 12 weeks after acetic acid treatment. However, no correlation between the progression of CKD and the decrease in renal blood flow was observed. Finally, repeated losartan administration attenuated the effects of acetic acid-induced renal injury. Our findings suggest that chronic kidney conditions associated with this model may be triggered by interstitial inflammation. Moreover, we suggest that this model is useful for understanding the pathophysiological mechanisms of CKD, and for evaluating the effects of therapeutic agents.